Recalibrating mobility and access towards spatial justice in Lilongwe - Mpanang'ombe, Wrixon (School of Architecture, Planning and Geomatics, 2025)
Lilongwe was planned as Malawi's post-colonial new capital city. The new city's master plan followed modernist planning and design principles transforming a small colonial town into a sprawling urban territory. To date, Lilongwe has maintained the spatial legacies of colonial and modernist planning. The city's form is currently characterised by a lower-density significantly formally planned core that retains the ideals of the master plan and higher-density less formally planned auto construction sprawling on the peripheries. The city does not have a formal public transport system, and most residents rely on informal (para)transit options such as minibuses and motorcycle taxis. The informal transit options are unscheduled, usually operate beyond the carrying capacity of the vehicles used, and appropriate street public space for pick-up and drop-off stops either complementing or competing with other uses of space such as walking and informal trade within the appropriated spaces. Consequently, the informal transit options are perceived as less convenient, uncomfortable or chaotic in the way they operate in street public spaces. Furthermore, the informal transit options are mostly unsupported by appropriate spatial infrastructure since they usually operate in spaces not specially designated and designed as transit stops. Additionally, the informal transit modes are all road-based yet the roads are mostly designed with less consideration for the transit uses and are primarily developed for private car mobility. Hence, private car mobility is considered the most convenient mode of moving around and accessing places in the city. However, many people particularly those with low incomes and those dependent on informal livelihoods cannot afford to own and use private cars. The lack of a formal public transit system as well as the general absence of transit-supportive urban infrastructure in Lilongwe contributes to spatial injustice as the many people who depend on informal transit face extra hurdles moving around and accessing places in the city as compared to the convenience of private car mobility. Moreover, spatial injustice manifests in how mobility infrastructure within street public space is allocated to the various competing or complementary modes of mobility, for instance, the usual provision of road paving for private car mobility without any allocation of infrastructure for pedestrians and transit. The allocation of space to the various mobility modes, in turn, impacts how people access various spaces and places together with the opportunities they present. Therefore, this research investigated how the modes and spaces that facilitate mobility, particularly informal transit, can be reimagined or recalibrated to foster spatial justice in Lilongwe. Additionally, the research investigated how the existing informal transit system (i.e., the modes and spaces that facilitate informal transit) can be leveraged to catalyse wider spatial justice goals, especially regarding people dependent on informal livelihoods. The research utilised an urban design approach to answer the main question: How can we reimagine mobility and accessibility to foster spatial justice in Lilongwe? Importantly, the study focused on understanding mobility and access with a special lens focused on people who use informal public transit and rely on informal livelihoods. In the context of Lilongwe, the research further approached spatial justice through the lens of historical spatial marginalisation emanating from the segregated colonial town. The spatial marginalisation initiated by the colonial town's master plan was carried further by the settlement typology and land use segregation of the capital city master plan. The capital city continues to shape the current geographies of spatial marginalisation with peripheral settlements housing poor residents who mostly rely on informal transit and depend on informal livelihoods. The research process involved a month of fieldwork in Lilongwe to understand the functioning of the modes and spaces facilitating the informal transit system and to learn about people's experiences with the informal transit system particularly those dependent on informal livelihoods. The findings from the fieldwork informed the contextual analysis which revealed the capacities, opportunities and constraints for urban design interventions. The research proposed an urban design framework that aims to enhance access to services and facilities, quality public open spaces, walkability and multi-scalar accessibility in the southern peripheries of the city as a pathway towards spatial justice for the peripheral areas. The urban design framework proposed a toolkit of spatial interventions grounded on principles of incrementalism, community stewardship, and high-impact low-tech. The proposed spatial interventions form the framework by leveraging the existing multi-modal informal transit system, the network of markets and informal trading strips, clusters of public facilities, and the blue-green network of streams and rivers. However, this report does not include the design propositions that were explored during the studio project, but focuses on an overview of the background research